Preparation method of nano silver powder for pressure-sensitive thermistor and electronic paste of nano silver powder

By introducing complexing agents and polymer graft polymer dispersants in the preparation process of nano-silver powder, combined with the use of surface modifiers, the problems of insufficient specific surface area and complex process in the prior art are solved, and the synthesis of high dispersion and high specific surface area nano-silver powder is achieved, simplifying the process and reducing costs.

CN119819939AActive Publication Date: 2025-04-15DONGFANG ELECTRIC CHENGDU INTELLIGENT TECH CO LTD +2
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510310255.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The specific surface area of ​​existing pressure-sensitive thermistor silver powder for high temperatures cannot reach more than 6m2/g, and the process is complicated, making it difficult to achieve industrial production.

Method used

The release rate of silver ions is controlled by introducing complexing agents, and the surface adsorption and spatial repulsion are used to perform surface adsorption and spatial repulsion. Combined with the use of surface modifiers, the washing process is simplified and the specific surface area and dispersion of nano silver powder are improved.

Benefits of technology

It realizes controllable and accurate synthesis of nano silver powder with high dispersion and high specific surface area, simplifies the process flow, reduces production costs, and improves production efficiency. It is suitable for electronic pastes for pressure-sensitive thermistors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819939A_ABST
    Figure CN119819939A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of nano silver powder for a pressure-sensitive thermistor and electronic paste of the nano silver powder, and belongs to the technical field of nano silver. The preparation method comprises the following steps: under a constant-temperature stirring condition, simultaneously adding a silver-containing oxidant solution and a complexing agent solution into a dispersing agent solution within 5-10 minutes, stirring for 5-20 minutes, then adding a reducing agent solution into a mixed solution within 1-20 minutes, continuously stirring for 5-30 minutes, washing the solution until the pH value of the solution is neutral, then adding a surface modifier solution into the solution, stirring for 10-30 minutes at a constant temperature, and drying to obtain the silver-containing composite material. The preparation method comprises the following steps: preparing a nano silver solution, washing until the conductivity of the solution is less than or equal to 100 [mu] s / cm, carrying out solid-liquid separation, drying and powdering the obtained silver powder to obtain the nano silver powder with the particle size of 20-400nm and the specific surface area of 5.0-14m < 2 > / g, and the nano silver powder has excellent particle size uniformity, is simple in synthesis process, low in production cost and short in period, can be widely applied to electronic paste for pressure-sensitive thermistors, and can be widely applied to electronic paste for pressure-sensitive thermistors, and the maximum particle size of the nano silver powder in a single batch can reach 80kg.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing nano silver powder for varistor thermistor and electronic paste thereof, and specifically relates to a method for preparing nano silver powder suitable for varistor thermistor and electronic paste prepared from the nano silver powder, belonging to the technical field of nano silver. Background Art

[0002] Nano silver powder has good electrical and thermal conductivity and is widely used in the electronics industry, mainly as a raw material for the production of piezoelectric ceramics, capacitors, potentiometers and other components, as well as conductive pastes and conductive inks. For high-temperature varistor thermistor silver powder, the surface brightness of the silver electrode is one of the key indicators, which has strict requirements on the specific surface area and surface activity of the silver powder required for the preparation of this type of silver paste. Generally speaking, the specific surface area of ​​this type of silver powder should be greater than 6m 2 / g, and has high dispersibility and uniformity. The formed silver paste has good leveling properties, which can ensure the good printing performance of the silver paste. After sintering, the surface density of the silver layer is higher and the silver layer is brighter.

[0003] In the prior art, Chinese patent CN103406550A discloses a method for preparing silver micropowder for electronic paste of varistor components, wherein a mixture of gelatin solution, ascorbic acid solution and soda ash solution is continuously and evenly placed in a silver nitrate solution, and the supernatant is extracted by precipitation. Finally, silver micropowder with a loose network structure is prepared. This silver powder has a relatively concentrated particle size distribution and a high surface activity, but the maximum specific surface area of ​​the powder can only reach 3.5m 2 / g. In addition, Chinese patent CN105880627A also discloses a method for preparing silver micropowder with precisely controlled specific surface area, wherein a mixture of polyvinyl alcohol and gelatin is used as a dispersant, and an excess of triethanolamine solution is slowly dripped into a silver nitrate solution whose pH is adjusted to 10-13 by sodium carbonate, and a silver micropowder with a specific surface area of ​​1.0-8.0 m2 is prepared at 25-40°C. 2 / g of silver powder. The silver micropowder prepared by this patent is mixed evenly in a certain proportion, which can achieve an ideal sintering effect, but its reaction is slow, resulting in a long production cycle, which is not conducive to actual industrial production. In addition, Chinese patent CN116329540A also discloses a nano silver powder for conductive slurry and its preparation process and application, which is prepared by slowly dropping hydrazine hydrate and pH regulator into a mixed solution of silver nitrate and a dispersant in sequence, heating to 30-60°C for reaction for 2-4 hours, and then centrifuging and filtering to obtain nano silver powder. This method uses a mixture of polyvinyl pyrrolidone, gum arabic, and gelatin to reduce the particle size of nano silver powder and prevent powder agglomeration, but its process operation is complicated and difficult to mass industrialize.

[0004] In summary, based on the performance requirements of existing high-temperature varistor thermistor silver powder (specific surface area greater than 6m 2 / g, high dispersibility, uniformity), currently no nano silver powder and conductive paste with industrial application prospects have been reported, for this reason, the present invention arises at the historic moment. Summary of the invention

[0005] The present invention aims to provide a method for preparing nano silver powder for varistor thermistor. In the preparation process, the release rate of silver ions is controlled by introducing a complexing agent. At the same time, the solubility of silver powder in solution is controlled by the adsorption of the ion base of the high molecular grafted polymer dispersant and the surface of the silver powder and the spatial repulsion effect of the grafted chain on the silver powder, thereby simplifying the washing process, saving costs, and realizing the controllable and precise synthesis of nano silver powder with high dispersibility and high specific surface area; the use of a surface modifier is also used to further reduce the hydrophobicity of the nano silver powder, and at the same time enhance the adaptability of the nano silver powder in electronic paste; and the nano silver powder prepared by the method has excellent particle size uniformity, and its synthesis process is simple, the production cost is low, the cycle is short, and the single batch can reach up to 80kg, which can be widely used in electronic paste for varistor thermistor. At the same time, the present invention also provides an electronic paste containing the nano silver powder for varistor thermistor obtained by the preparation method.

[0006] The present invention is achieved through the following technical solution: A method for preparing nano silver powder for varistor thermistor, comprising the following steps: S1. Liquid preparation: dissolving a silver-containing oxidant in pure water to prepare a silver-containing oxidant solution with a silver ion concentration of 0.1 to 3 mol / L, dissolving a complexing agent in pure water to prepare a complexing agent solution with a mass volume concentration of 12 to 300 g / L, dissolving a dispersant in pure water, methanol or ethanol to prepare a dispersant solution with a mass fraction of 1 to 10%, dissolving a reducing agent in pure water to prepare a reducing agent solution with a mass volume concentration of 100 to 900 g / L, and dissolving a surface modifier in ethanol to prepare a surface modifier solution with a mass fraction of 3 to 10%; S2. Reaction: Under constant temperature stirring conditions, the silver-containing oxidant solution and the complexing agent solution are simultaneously added to the dispersant solution within 5 to 10 minutes, stirred for 5 to 20 minutes, and then the reducing agent solution is added to the mixed solution within 1 to 20 minutes, and stirring is continued for 5 to 30 minutes; S3 washing: deionized water was added to the mixed solution obtained in step S2, and then the supernatant was extracted for washing after standing and settling until the pH of the solution was neutral; S4. Modification and washing: adding a surface modifier solution to the solution obtained in step S3, stirring at a constant temperature for 10 to 30 minutes, and then adding deionized water to the solution, and then standing and settling to extract the clear liquid for washing until the conductivity of the solution is ≤100μs / cm and the solid-liquid separation is performed; S5. Drying and pulverizing: After the silver powder obtained by solid-liquid separation in step S4 is dried and pulverized, the particle size is 20 to 400 nm and the specific surface area is 5.0 to 14 m 2 / g of nano silver powder.

[0007] The silver-containing oxidizing agent is silver nitrate.

[0008] The complexing agent is selected from at least one of sodium hydroxide, potassium hydroxide, sodium chloride, potassium chloride, sodium carbonate, potassium carbonate and ammonia water.

[0009] The dispersant is a high molecular graft polymer, and its usage is 0.1-5% of the silver content in the silver-containing oxidant.

[0010] The reducing agent is selected from at least one of formaldehyde, sodium borohydride, ascorbic acid, hydrazine hydrate, triethanolamine and glucose.

[0011] The surface modifier is selected from one of lauric acid, oleic acid, ricinoleic acid, palmitic acid, stearic acid, palmitic acid and arachidic acid, and its usage is 0.5-3% of the silver content in the silver-containing oxidant.

[0012] The constant temperature stirring conditions are a water bath temperature of 20 to 80° C. and a mechanical stirring of 200 to 350 rpm.

[0013] The drying and pulverization is carried out by drying in a blast oven at 80° C. for 24 to 36 hours and then pulverizing using a crushing and pulverizing device.

[0014] An electronic paste for a varistor thermistor contains nano silver powder prepared by the method described above.

[0015] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The present invention is completely different from the existing preparation principle of nano silver powder. In the liquid phase synthesis process, a complexing agent is introduced to control the release rate of silver ions, thereby realizing the regulation of silver atoms from nucleation to growth; at the same time, a high molecular graft polymer dispersant is introduced to utilize the strong adsorption effect of its ion-based main chain on the surface of silver powder and the spatial repulsion effect of different grafted chains on silver powder, thereby achieving rapid coating of silver powder and control of its solubility in solution, ensuring the high dispersibility of silver powder and simplifying the washing process of powder.

[0016] (2) In the method of the present invention, the use of a surface modifier further enhances the hydrophobicity of the silver powder, making the powder easier to settle, thereby increasing the silver powder collection rate and reducing the equipment cost required for the washing process; on the other hand, the use of a surface modifier enhances the adaptability of the nano silver powder in the electronic slurry, so that a single powder still has a good application effect in a slurry system with a silver content of 30 to 80%.

[0017] (3) The preparation process of the method of the present invention is simple, the production cycle is short, and the cost is low. It can achieve the production of 80 kg of nano silver powder in a single batch, has strong repeatability, and can achieve industrial-scale production.

[0018] In summary, the present invention discloses a new preparation method of nano silver powder for varistor thermistor. In the reaction process, by reasonably selecting the types and amounts of complexing agent and dispersant, controllable and precise synthesis of nano silver powder with high dispersibility and high specific surface area can be achieved. The use of surface modifier can simplify the washing process, reduce production cost, and enhance the application performance of nano silver powder in electronic paste. The preparation process of the method is simple and easy to control, and large-scale stable production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is an electron microscope image of the nano silver powder in Example 1 of the present invention.

[0020] Figure 2 This is an electron microscope image of the nano silver powder in Example 2 of the present invention.

[0021] Figure 3 This is an electron microscope image of the nano silver powder in Example 3 of the present invention.

[0022] Figure 4 This is an electron microscope image of the nano silver powder in Example 4 of the present invention.

[0023] Figure 5 It is an electron microscope image of the nano silver powder in Comparative Example 1 of the present invention.

[0024] Figure 6 It is an electron microscope image of the nano silver powder in Comparative Example 2 of the present invention.

[0025] Figure 7 It is an electron microscope image of the nano silver powder in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0026] The invention objectives, technical solutions and beneficial effects of the present invention are further described in detail below.

[0027] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the claimed invention, and unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs.

[0028] The present invention aims to solve the relevant performance requirements of the existing nano silver powder for varistor thermistor, and provides a new method for preparing nano silver powder. The nano silver powder is mainly prepared by a silver-containing oxidant, a complexing agent, a dispersant, a reducing agent and a surface modifier through a special reaction step, wherein the release rate of silver atoms in the reaction system can be controlled by the appropriate selection of the complexing agent, and the dispersant of the high molecular graft polymer is matched to achieve the controllable and precise synthesis of nano silver powder with high dispersibility and high specific surface area through the adsorption of ionic groups on the surface of the powder and the control of the solubility in the solvent and the graft chain that imparts the spatial repulsion effect. The use of the surface modifier can further reduce the hydrophobicity of the nano silver powder and enhance the adaptability of the nano silver powder in the electronic paste. Therefore, the nano silver powder prepared by the method has excellent particle size uniformity, so that the single powder still has a good application effect in the paste system with a silver content of 30 to 80%.

[0029] The technical solution of the present invention can be further summarized as follows: First, prepare the following material solutions: Silver nitrate solution: Dissolve silver nitrate in pure water to prepare a silver nitrate solution with a silver ion concentration of 0.1 to 3 mol / L.

[0030] Complexing agent solution: dissolve the complexing agent in pure water to prepare an alkaline solution with a mass volume concentration of 12 to 300 g / L. The complexing agent can be selected from at least one of sodium hydroxide, potassium hydroxide, sodium chloride, potassium chloride, sodium carbonate, potassium carbonate, and ammonia water.

[0031] Dispersant solution: dissolve the high molecular graft polymer in pure water, methanol or ethanol to prepare a dispersant solution with a mass fraction of 1 to 10%. The amount of the high molecular graft polymer used is 0.1 to 5% of the silver content in the silver-containing oxidant. Optional high molecular graft polymers include: poly (ethyleneimine-graft-polyhydroxy ester), sodium polyacrylate grafted starch, cellulose grafted polyacrylic acid, cellulose-polyacrylamide grafted copolymer, starch-acrylic acid grafted copolymer, starch-acrylonitrile grafted copolymer, carboxymethyl cellulose-acrylic acid grafted copolymer and other high molecular graft polymers.

[0032] Reducing agent solution: dissolving the reducing agent in pure water to prepare a reducing agent solution with a mass volume concentration of 100 to 900 g / L, wherein the reducing agent can be selected from at least one of formaldehyde, sodium borohydride, ascorbic acid, hydrazine hydrate, triethanolamine, and glucose.

[0033] Surface modifier solution: dissolve the surface modifier in ethanol to prepare a surface modifier solution with a mass fraction of 3% to 10%. The surface modifier can be selected from one of lauric acid, oleic acid, ricinoleic acid, palmitic acid, stearic acid, palmitic acid, and arachidic acid, and the amount of the surface modifier used is 0.5 to 3% of the silver content in the silver-containing oxidant.

[0034] Secondly, reaction and washing: under constant temperature stirring conditions, add the above silver nitrate solution and complexing agent solution to the dispersant solution at the same time within 5 to 10 minutes, stir for 5 to 20 minutes, add the reducing agent solution to the mixed solution within 1 to 20 minutes, continue stirring for 5 to 30 minutes, add deionized water and wash several times by static sedimentation to extract the clear liquid until the pH of the supernatant is neutral.

[0035] Then, modification and washing: add the surface modifier solution to the solution obtained by washing, stir at a constant temperature for 10 to 30 minutes, add deionized water and wash several times by static sedimentation and extraction of clear liquid, until the conductivity of the supernatant is ≤100μs / cm to separate the solid and liquid.

[0036] Finally, drying and pulverizing: the silver powder obtained by solid-liquid separation is placed in an oven at 80°C for 24 to 36 hours and pulverized by crushing and pulverizing equipment to obtain highly dispersed nano silver powder with a particle size range of 20 to 400 nm and a specific surface area of ​​5.0 to 14 m 2 / g, and the silver powder has a good application effect in electronic paste with a silver content of 30-80%, meeting the actual application needs of varistors.

[0037] In order to achieve effective control of the specific surface area and dispersibility of the silver powder in the present invention, during the preparation process, it is necessary to adjust factors such as the type and amount of the complexing agent and the high molecular graft polymer, the type and addition time of the reducing agent, and the type and amount of the modifier. Different combinations of factors can obtain silver powders with different specific surface areas and dispersities.

[0038] The drying time of the powder in the present invention is 24 to 36 hours. In specific operation, the drying time can be determined according to the water content of the powder. The silver powder obtained in the present invention has a small size and a high surface energy. Therefore, the powder is in a block shape macroscopically after drying and needs to be broken up by a special crushing and pulverizing device to restore its original dispersion state. This process does not affect the dispersibility of the powder itself.

[0039] The specific implementation modes of the present invention are described below in conjunction with the embodiments. Of course, the protection scope of the present invention is not limited to the following embodiments.

[0040] It should be noted that the following embodiments and comparative examples are all based on the production of 20 kg of silver powder in a single batch. In actual implementation, the same proportion can be enlarged or reduced according to different conditions such as the actual production equipment. For example, 1 kg, 10 kg or 80 kg of silver powder can be produced in a single batch. In addition, the single batch production of 20 kg of silver powder in the present invention refers to the theoretical content of silver in the silver nitrate used. In the actual production process, due to the presence of dispersants and modifiers, the amount of silver powder collected will be slightly more than 20 kg.

[0041] Example 1: Preparation of Nano Silver Powder (20 kg) Accurately weigh 31.53 kg of silver nitrate solid and dissolve it in 200 kg of deionized water, stir and keep the temperature at 40°C to prepare a silver nitrate solution for later use; Accurately weigh 15 kg of sodium hydroxide solid and dissolve it in 85 kg of deionized water, stir and keep the temperature at 40°C to prepare a sodium hydroxide solution for later use; Accurately weigh 400g of high molecular weight graft polymer and dissolve it in 20kg of deionized water, stir and keep the temperature at 40°C to prepare a dispersant aqueous solution for later use; Accurately weigh 33.44 kg of anhydrous glucose solid and dissolve it in 100 kg of deionized water, stir and keep the temperature at 40°C to prepare a glucose solution for later use; Dissolve 200 g of lauric acid in 1 kg of ethanol and stir until colorless and transparent to obtain a lauric acid solution for later use.

[0042] At a water bath temperature of 40°C and a stirring speed of 250rpm, sodium hydroxide solution and silver nitrate solution were added to the dispersant solution within 9 minutes, and after constant temperature stirring for 10 minutes, glucose solution was added to the mixed solution within 15 minutes, and after constant temperature stirring for 20 minutes, deionized water was added, and the supernatant was extracted after standing and settling for 20 minutes, and the washing was repeated several times until the pH of the supernatant was neutral. Then, lauric acid solution was added thereto, and after constant temperature stirring for 30 minutes, deionized water was added, and the supernatant was extracted after standing and settling for 20 minutes, and the washing was repeated several times until the conductivity of the supernatant was <100us / cm, and the solid-liquid separation was achieved.

[0043] The silver powder obtained by solid-liquid separation was placed in an oven at 80°C for 28 hours and then pulverized using a crushing and pulverizing device to obtain a particle size range of 50 to 200 nm and a specific surface area of ​​9.8 m 2 / g of nano silver powder (see Figure 1 ).

[0044] Example 2: Preparation of Nano Silver Powder (20 kg) Accurately weigh 31.53 kg of silver nitrate solid and dissolve it in 200 kg of deionized water, stir and keep the temperature at 30°C to prepare a silver nitrate solution for later use; Accurately weigh 7.87 kg of sodium hydroxide solid and dissolve it in 98 kg of deionized water, stir and keep the temperature at 30°C to prepare a sodium hydroxide solution for later use; Accurately weigh 600g of high molecular graft polymer and dissolve it in 50kg of deionized water, stir and keep the temperature at 30°C to prepare a dispersant aqueous solution for later use; Accurately weigh 11.6 kg of 80% hydrazine hydrate and dissolve it in 11.6 kg of deionized water, stir and keep the temperature at 30°C to prepare a hydrazine hydrate solution for later use; Dissolve 160 g of oleic acid in 0.5 kg of ethanol and stir until the solution becomes colorless and transparent to obtain an oleic acid solution for later use.

[0045] At a water bath temperature of 30°C and a stirring speed of 250 rpm, sodium hydroxide solution and silver nitrate solution were added to the dispersant solution within 10 minutes, and after constant temperature stirring for 5 minutes, glucose solution was added to the mixed solution within 5 minutes, and after constant temperature stirring for 5 minutes, deionized water was added, and the supernatant was extracted after standing and settling for 10 minutes, and the washing was repeated several times until the pH of the supernatant was neutral. Then, oleic acid solution was added thereto, and after constant temperature stirring for 30 minutes, deionized water was added, and the supernatant was extracted after standing and settling for 30 minutes, and the washing was repeated several times until the conductivity of the supernatant was <100us / cm, and the solid-liquid separation was achieved.

[0046] The silver powder obtained by solid-liquid separation was placed in an oven at 80°C for 24 hours for drying, and then pulverized by a crushing and pulverizing device to obtain a particle size range of 200-400nm and a specific surface area of ​​5.5m 2 / g of nano silver powder (see Figure 2 ).

[0047] Example 3: Preparation of Nano Silver Powder (20 kg) Accurately weigh 31.53 kg of silver nitrate solid and dissolve it in 200 kg of deionized water, stir and keep the temperature at 80°C to prepare a silver nitrate solution for later use; Accurately weigh 10.12 kg of sodium hydroxide solid and dissolve it in 138 kg of deionized water, stir and keep the temperature at 80°C to prepare a sodium hydroxide solution for later use; Accurately weigh 1000g of high molecular weight graft polymer and dissolve it in 60kg of deionized water, stir and keep the temperature at 80°C to prepare a dispersant aqueous solution for later use; Accurately weigh 13.83 kg of triethanolamine and dissolve it in 20 kg of deionized water. Stir and keep the temperature at 80°C to prepare a triethanolamine solution for later use. Dissolve 400 g of arachidic acid in 1 kg of ethanol and stir until colorless and transparent to obtain an arachidic acid solution for later use.

[0048] At a water bath temperature of 80°C and a stirring speed of 200rpm, add the sodium hydroxide solution and the silver nitrate solution to the dispersant solution within 10min, stir at a constant temperature for 20min, add the triethanolamine solution to the mixed solution within 3min, stir at a constant temperature for 30min, add deionized water, let it stand for 30min, extract the supernatant, and repeat the washing several times until the pH of the supernatant is neutral. Then add the arachidic acid solution, stir at a constant temperature for 30min, add deionized water, let it stand for 30min, extract the supernatant, and repeat the washing several times until the conductivity of the supernatant is <100us / cm, and the solid-liquid separation is achieved.

[0049] The silver powder obtained by solid-liquid separation was placed in an oven at 80°C for 36 hours and then pulverized using a crushing and pulverizing device to obtain a particle size range of 90 to 370 nm and a specific surface area of ​​7.1 m 2 / g of nano silver powder (see Figure 3 ).

[0050] Example 4: Preparation of Nano Silver Powder (20 kg) Accurately weigh 31.53 kg of silver nitrate solid and dissolve it in 150 kg of deionized water, stir and keep the temperature at 45°C to prepare a silver nitrate solution for later use; Accurately weigh 7.87 kg of sodium hydroxide solid and dissolve it in 85 kg of deionized water, stir and keep the temperature at 45°C to prepare a sodium hydroxide solution for later use; Accurately weigh 1000g of high molecular weight graft polymer and dissolve it in 40kg of deionized water, stir and keep the temperature at 45°C to prepare a dispersant aqueous solution for later use; Accurately weigh 20 kg of ascorbic acid solid and dissolve it in 110 kg of deionized water, stir and keep the temperature at 45°C to prepare an ascorbic acid solution for later use; Dissolve 200g of palmitic acid in 1kg of ethanol and stir until it becomes colorless and transparent to obtain a palmitic acid solution for later use.

[0051] At a water bath temperature of 45°C and a stirring speed of 200rpm, add the sodium hydroxide solution and the silver nitrate solution to the dispersant solution within 10 minutes, stir at a constant temperature for 15 minutes, add the ascorbic acid solution to the mixed solution within 5 minutes, stir at a constant temperature for 5 minutes, add deionized water, let it stand for 30 minutes, extract the supernatant, and repeat the washing several times until the pH of the supernatant is neutral. Then add the palmitic acid solution, stir at a constant temperature for 30 minutes, add deionized water, let it stand for 30 minutes, extract the supernatant, and repeat the washing several times until the conductivity of the supernatant is <100us / cm, and the solid-liquid separation is achieved.

[0052] The silver powder obtained by solid-liquid separation was placed in an oven at 80°C for 32 hours for drying, and then pulverized by crushing and pulverizing equipment to obtain a particle size range of 50 to 330 nm and a specific surface area of ​​8.2 m 2 / g of nano silver powder (see Figure 4 ).

[0053] Comparative Example 1: This comparative example uses the same solution as in Example 1, including silver nitrate solution, sodium hydroxide solution, dispersant aqueous solution, glucose solution and lauric acid solution, and the following reaction process is used during preparation: At a water bath temperature of 40°C and a stirring speed of 250rpm, add the glucose solution and the silver nitrate solution to the dispersant solution within 9 minutes, stir at a constant temperature for 10 minutes, add the sodium hydroxide solution to the mixed solution within 15 minutes, stir at a constant temperature for 20 minutes, add deionized water, let it stand for 20 minutes, extract the supernatant, and repeat the washing several times until the pH of the supernatant is neutral. Then add the lauric acid solution, stir at a constant temperature for 30 minutes, add deionized water, let it stand for 20 minutes, extract the supernatant, and repeat the washing several times until the conductivity of the supernatant is <100us / cm, and the solid-liquid separation is achieved.

[0054] The silver powder obtained by solid-liquid separation was placed in an oven at 80°C for 28 hours and then pulverized using a crushing and pulverizing device to obtain a particle size range of 110 to 5400 nm and a specific surface area of ​​5.1 m 2 / g of nano silver powder (see Figure 5 ).

[0055] Comparative Example 2: The difference between this comparative example and Example 1 is that no dispersant solution is used, and the remaining solutions and preparation processes are exactly the same, as follows: At a water bath temperature of 40°C and a stirring speed of 250rpm, add the sodium hydroxide solution to the silver nitrate solution within 9 minutes, stir at a constant temperature for 10 minutes, add the glucose solution to the mixed solution within 15 minutes, stir at a constant temperature for 20 minutes, add deionized water, let it stand for 20 minutes, extract the supernatant, and repeat the washing several times until the pH of the supernatant is neutral. Then add the lauric acid solution, stir at a constant temperature for 30 minutes, add deionized water, let it stand for 20 minutes, extract the supernatant, and repeat the washing several times until the conductivity of the supernatant is <100us / cm, and the solid-liquid separation is achieved.

[0056] The silver powder obtained by solid-liquid separation was placed in an oven at 80°C for 28 hours and then pulverized using a crushing and pulverizing device to obtain a particle size range of 70 to 4250 nm and a specific surface area of ​​6.3 m 2 / g of nano silver powder (see Figure 6 ).

[0057] Comparative Example 3: The difference between this comparative example and Example 1 is that the lauric acid solution is replaced by KH550 solution, and the remaining solutions and preparation processes are exactly the same, as follows: Preparation of KH550 solution: Dissolve 200g KH550 in 1kg ethanol and stir until colorless and transparent to obtain KH550 solution.

[0058] At a water bath temperature of 40°C and a stirring speed of 250rpm, add the sodium hydroxide solution to the silver nitrate solution within 9 minutes, stir at a constant temperature for 10 minutes, add the glucose solution to the mixed solution within 15 minutes, stir at a constant temperature for 20 minutes, add deionized water, let it stand for 20 minutes, extract the supernatant, and repeat the washing several times until the pH of the supernatant is neutral. Then add the KH550 solution, stir at a constant temperature for 30 minutes, add deionized water, let it stand for 20 minutes, extract the supernatant, and repeat the washing several times until the conductivity of the supernatant is <100us / cm, and the solid-liquid separation is achieved.

[0059] The silver powder obtained by solid-liquid separation was placed in an oven at 80°C for 28 hours and then pulverized using a crushing and pulverizing device to obtain a particle size range of 140 to 17930 nm and a specific surface area of ​​4.5 m 2 / g of nano silver powder (see Figure 7 ).

[0060] It can be seen from Examples 1 to 4 that the present invention can form nano silver powder with high dispersibility and high specific surface area by combining a complexing agent and a high molecular graft polymer. The introduction of the complexing agent can control the release rate of silver ions. When the order of adding the complexing agent is changed (see Comparative Example 1), even if a high molecular graft polymer is used, it is impossible to achieve rapid coating and solubility of silver powder in the system, and it is impossible to ensure the control of high dispersion performance of silver powder; when the high molecular graft polymer is omitted (see Comparative Example 2), even if the release rate of silver ions can be controlled, the dispersion performance of silver powder in the system cannot be controlled, so that the powder is adhered and agglomerated due to high surface energy; the present invention can further reduce the hydrophobicity of nano silver powder and enhance the adaptability of nano silver powder in electronic paste by using a surface modifier solution. If it is replaced with other solutions (see Comparative Example 3), it may cause serious adhesion and agglomeration of the powder, and the powder still presents hydrophilicity, which is not conducive to the subsequent washing process and affects the adaptability and application performance of the powder in the electronic paste.

[0061] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for preparing nano silver powder for varistor thermistor, characterized in that: The following steps are involved: S1. Liquid preparation: dissolving a silver-containing oxidant in pure water to prepare a silver-containing oxidant solution with a silver ion concentration of 0.1 to 3 mol / L, dissolving a complexing agent in pure water to prepare a complexing agent solution with a mass volume concentration of 12 to 300 g / L, dissolving a dispersant in pure water, methanol or ethanol to prepare a dispersant solution with a mass fraction of 1 to 10%, dissolving a reducing agent in pure water to prepare a reducing agent solution with a mass volume concentration of 100 to 900 g / L, and dissolving a surface modifier in ethanol to prepare a surface modifier solution with a mass fraction of 3 to 10%; S2. Reaction: Under constant temperature stirring conditions, the silver-containing oxidant solution and the complexing agent solution are simultaneously added to the dispersant solution within 5 to 10 minutes, stirred for 5 to 20 minutes, and then the reducing agent solution is added to the mixed solution within 1 to 20 minutes, and stirring is continued for 5 to 30 minutes; S3 washing: deionized water was added to the mixed solution obtained in step S2, and then the supernatant was extracted for washing after standing and settling until the pH of the solution was neutral; S4. Modification and washing: adding a surface modifier solution to the solution obtained in step S3, stirring at a constant temperature for 10 to 30 minutes, and then adding deionized water to the solution, and then standing and settling, extracting the clear liquid for washing until the conductivity of the solution is ≤100μs / cm, and solid-liquid separation is performed; S5. Drying and pulverizing: After the silver powder obtained by solid-liquid separation in step S4 is dried and pulverized, the particle size is 20 to 400 nm and the specific surface area is 5.0 to 14 m 2 / g of nano silver powder.

2. The preparation method according to claim 1, characterized in that: The silver-containing oxidizing agent is silver nitrate.

3. The preparation method according to claim 1, characterized in that: The complexing agent is selected from at least one of sodium hydroxide, potassium hydroxide, sodium chloride, potassium chloride, sodium carbonate, potassium carbonate and ammonia water.

4. The preparation method according to claim 1, characterized in that: The dispersant is a high molecular graft polymer, and its usage is 0.1-5% of the silver content in the silver-containing oxidant.

5. The preparation method according to claim 1, characterized in that: The reducing agent is selected from at least one of formaldehyde, sodium borohydride, ascorbic acid, hydrazine hydrate, triethanolamine and glucose.

6. The preparation method according to claim 1, characterized in that: The surface modifier is selected from one of lauric acid, oleic acid, ricinoleic acid, palmitic acid, stearic acid, palmitic acid and arachidic acid, and its usage is 0.5-3% of the silver content in the silver-containing oxidant.

7. The preparation method according to claim 1, characterized in that: The constant temperature stirring conditions are a water bath temperature of 20 to 80° C. and a mechanical stirring of 200 to 350 rpm.

8. The preparation method according to claim 1, characterized in that: The drying and pulverization is carried out by drying in a blast oven at 80° C. for 24 to 36 hours and then pulverizing using a crushing and pulverizing device.

9. An electronic paste for a varistor thermistor, characterized in that: The electronic paste contains nano silver powder obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • High-dispersion silver powder and solar battery electrode conductive silver paste

    CN102139368A

  • Preparation method for micro-nano silver powder with controllable particle size

    CN111889695A

  • Preparation method of super-hydrophobic high-dispersity silver powder

    CN115846678A

  • Preparation method of nano silver powder

    CN119260014A

  • Nano silver powder for low-temperature sintering type water-based polyester-based conductive paste and preparation method of nano silver powder

    CN119304201A